High-throughput front and rear side metallization of silicon solar cells using rotary screen printing. (September 2017) - Lorenz, Andreas; Münzer, Anna; Lehner, Martin; Greutmann, Roland; Brocker, Heinz; Reinecke, Holger; Clement, Florian
Abstract: Rotational screen printing (RSP) has recently attracted attention as a highly promising high-throughput alternative for the metallization of Silicon solar cells. Compared to other metallization approaches, RSP is already a well-developed printing method which has been used for various industrial applications during the last decades. The unique benefit of this technology is the ability to apply a thick film metallization combined with a high throughput. Within the present work, we will discuss the actual achievements and challenges of this approach. We show the results of Aluminium back surface solar cells with a RSP rear side metallization and a mean conversion efficiency of η = 19.4 % compared to reference solar cells with flatbed screen printed rear side metallization and a conversion efficiency of η = 19.3 %. We further investigate the properties of fine line cylinder screens used for RSP and conventional flatbed screen printing. Using RSP with a fine line cylinder screen, we printed contact fingers with a mean width down wf = 61 µm. Finally, we discuss the path to a further optimization of this highly promising approach.